Ligands and Receptors Involved in the Sperm-Zona Pellucida Interactions in Mammals - Tumova, Lucie; Zigo, Michal; Sutovsky, Peter; Sedmikova, Marketa; Postlerova, Pavla (Cells, 2021)
Sperm-zona pellucida (ZP) interaction, involving the binding of sperm surface ligands to complementary carbohydrates of ZP, is the first direct gamete contact event crucial for subsequent gamete fusion and successful fertilization in mammals. It is a complex process mediated by the coordinated engagement of multiple ZP receptors forming high-molecular-weight (HMW) protein complexes at the acrosomal region of the sperm surface. The present article aims to review the current understanding of sperm-ZP binding in the four most studied mammalian models, i.e., murine, porcine, bovine, and human, and summarizes the candidate ZP receptors with established ZP affinity, including their origins and the mechanisms of ZP binding. Further, it compares and contrasts the ZP structure and carbohydrate composition in the aforementioned model organisms. The comprehensive understanding of sperm-ZP interaction mechanisms is critical for the diagnosis of infertility and thus becomes an integral part of assisted reproductive therapies/technologies.
Keywords: ZP-ligands; Animals; Mammals; spermie; Spermatozoa; Membrane Glycoproteins; lidé; zona pellucida; Zona Pellucida; Ligands; savci; Male; receptory buněčného povrchu; gamete interaction; mezibuněčná komunikace; Cell Communication; sperm-ZP receptors; Receptors, Cell Surface; membránové glykoproteiny; mužské pohlaví; zvířata; spermatozoa; ligandy; Humans